Case Study of ITB Cirebon GOR Building Beam Structure Checking Against Torsion Loads - Ryanto, Muhamad (GoAcademica Research & Publishing, 2024)
In this analytical study, a building structure planning analysis will be carried out as well as checking the beam structure for torsional loads at the ITB Sports Arena (GOR) Building located in Cirebon. Analysis and planning refer to SNI 1726:2019, SNI 2847:2019 and SNI 2020. Modeling analysis and checking of torsion beams using the SAP2000 program as well as manual calculation analysis. Torque is almost the same as design for bending and shearing when the factored torsional moment load applied to a section exceeds the torsional resistance that can be provided by the concrete section itself. The results of the analysis and calculation of the beam structure using the SAP2000 program were obtained: from reinforcement calculations and analysis using SAP2000 software on the beam structure, as well as checking the beam for torsion, the value was taken with the largest torsion force of 91.3673 KN for beam B1A (600 x 450): Top reinforcement with supports 5D22, field 3D22, Support 3D22 ; Bottom reinforcement with support 4D22, Field 4D22, Support 4D22; Web reinforcement with support 4D16, Field 4D16, Support 4D16; using 3 foot stirrups with support D13-100, Field D13-150, Support 13-100.